Politeness strategies and power relations in Zendaya and Nicole Kidman youtube channel interviews - Daniah Farah; Hilmi Akmal; Muhammad Agus Suriadi (Journal of Language and Pragmatics Studies, 2025)
This research was conducted to examine the politeness strategies and power relations found in the “Actors on Actors” interview between Zendaya and Nicole Kidman on the Variety YouTube channel. The analysis was based on Brown and Levinson’s (1987) politeness strategies theory and Brown and Gilman’s (1960) power and solidarity theory. The objectives of the study were: (1) To identify the politeness strategies employed by Zendaya and Nicole Kidman in interviews on the Variety YouTube channel (2) To analyze how the power relations influenced politeness strategies in interviews with Zendaya and Nicole Kidman on the Variety YouTube channel. A qualitative method was applied, with data collected through purposive sampling. A total of 47 politeness strategies were identified in the interview between Nicole Kidman and Zendaya. Positive politeness appeared most frequently (34 times), followed by negative politeness (7), bald on-record (4), and off-record strategies (2), with no instances of don’t do the FTA. The dominance of positive politeness indicates that the interaction is primarily characterized by solidarity, warmth, and mutual respect. Despite differences in age and experience, both speakers maintained an equal and friendly atmosphere. Their shared identity as professional actors enabled them to connect through a mutual understanding of the industry, the artistic process, and the emotional demands of their work, which in turn strengthened the solidarity expressed throughout the interaction.